Analisis Permasalahan Pembelajaran dan Upaya Inovasi di Kelas 5 Yayasan Al-Hidayah - Julia Amelia Sormin; Eva Betty Simanjuntak; Afrida Hanum Lubis; Najwa Fadhilah Siregar; Nabila Olivia (Jurnal Bintang Pendidikan Indonesia, 2025)
This study aims to analyze the learning difficulties experienced by fifth-grade students at Yayasan Al-Hidayah and identify innovative solutions in the learning process. The research uses a descriptive quantitative method with data collected through questionnaires. The results indicate that students still face challenges in understanding the material, primarily due to the fast pace of the teacher's explanations, a lack of supporting media and teaching aids, and limited learning facilities. The most difficult subjects for students to understand are Mathematics, followed by English and Science. Despite these challenges, parental involvement in supporting the learning process is relatively good, and students tend to prefer interactive learning, such as educational games, group discussions, experiments, and the use of digital media. Based on these findings, there is a need for innovation in learning, focusing on technology-based learning, the use of more varied teaching aids, and the application of creative strategies to enhance motivation, understanding, and student learning outcomes. Such innovations are expected to provide more engaging and effective learning experiences for students, addressing the difficulties they encounter in learning.